On some topics in the theory of infinite dimensional linear groups - Dixon, M.R.; Kurdachenko, L.A.; Semko, N.N.; Subbotin, I.Ya. (Algebra and Discrete Mathematics, 2020)
In this paper we present a synopsis of some recent results concerned with infinite dimensional liner groups, including generalizations of irreducibility, the central dimension of a linear group, groups with finite dimensional orbits and the maximal and minimal conditions on subgroups of infinite central dimension.